AN ANALYSIS ON THE IMPLEMENTATION OF THE INTEGRATED GUIDANCE POST (POSBINDU) ACTIVITIES FOR NON-COMMUNICABLE DISEASES AT BOGOR CITY IN 2018 - Alfiyah, Alfiyah; Pujiyanto, Pujiyanto (UI Scholars Hub, 2019)
One of the endeavors that the government has done to prevent and control non-communicable diseases (NCD) by increasing community participation in the early detection of NCDs is the NCD Integrated Guidance Post (Posbindu). However, in 2017, only 12.96% of the residents in Bogor City accessed it. This meant that the 30% target was not reached. The in this study, we researched the implementation of the NCD Posbindu at Bogor City. Data was gathered through in-depth interviews, Focus Group Discussion (FGD), documentary research, and observations. Eleven informants was interviewed and 24 informants was involved in the FGD. Two NCD Posbindus was observed at Mekarwangi and Cipaku Public Health Centers (PHC). We discovered that the standards and policies have supported the program, but not all the informants were aware of the targets of the program; there were also problems in the number and abilities of the human resources involved, ineffective communication between the cadres, in the coordination between the cadres, and lack of support from local public figures. The program had adequate funding from the regional budget, the Operational Health Aid Funds, and donations from the community. Although more funds are necessary for the promotion and prevention part of the program. We recommend that new cadres are recruited and trained, and that a reward system is used to provide motivation for the cadres.